Working with Anangu (Aboriginal people) with disabilities from remote Central Australia. Navigating multiple expectations: "sandpaper and polyfilla". Issue 2 (3rd July 2022) - Barton, Rebecca; Dew, Angela; Ryall, Lee; Jensen, Heather; Taylor, Kerry; Lincoln, Michelle; Gilroy, John; Flood, Vicki; McRae, Kim
Abstract: The need for cultural safety in the delivery of health and disability services to Aboriginal people is being increasingly recognised. Those delivering services in remote communities face the challenge of providing culturally safe and responsive services with limited resources and a host of geographical and infrastructure challenges. Earlier research identified the importance of sharing knowledge and working together to deliver services to Aboriginal people (An angu) with disabilities in Central Australia, and workers are also bound by funding and policy guidelines as they deliver services. However, little is known about how workers navigate these different social and cultural expectations and accountabilities when working with An angu. Interviews were conducted with 47 workers from 16 service provider agencies responsible for delivering services to An angu with disabilities from the Ngaanyatjarra Pitjantjatjara Yankunytjatjara Lands. Workers invested significant time and energy in strategies to navigate these different contexts, much of which was not formally acknowledged or supported at a system level. Strategies employed included: fostering cultural knowledge and collaborative relationships, delivering creative and flexible services, and critical reflection on practice. Cultural safety and responsiveness of workers is important and warrants investment of time and effort. However, relying on workers to "soften the edges" and create an ostensible fit between bureaucracy and meeting the needs of An angu with disabilities creates unrecognised burden for workers and fails to address the systemic beliefs, values and social and economic disadvantage that underpin an inadequate support system.